The genetically programmed rhythmic alteration of diurnal gene expression in the aged Arabidopsis leaves - Jung, Sukjoon; Kim, Hyunmin; Lee, Juhyeon; Kang, Myeong Hoon; Kim, Jungyeon; Kim, Jong Kyoung; Lim, Pyung Ok; Nam, Hong Gil (Frontiers in Plant Science, 2024)
The circadian clock regulates the daily pattern of temporal gene expression. In Arabidopsis, aging is associated with a shortening of the endogenous period of circadian rhythms under circadian conditions. However, the functional link between the circadian clock and aging under diurnal conditions and its physiological relevance remain elusive. In this study, we investigate and characterize the effect of aging on the waveforms of rhythmic gene expression patterns under light/dark cycles. Our analysis revealed that the diurnal rhythmic patterns of core clock genes undergo significant rhythmic alteration with phase shift and change of waveforms in aged plants compared to younger plants. Transcriptomic analysis indicated that this age-dependent rhythmic alteration occurs not only in core clock genes but also globally. Due to the rhythmic alteration patterns of the diurnal rhythmic gene expression, aged plants experience subjectively a shorter day and longer night. We also observed that genetic mutants of core clock component genes exhibited broadly yet distinctively altered changes in diurnal rhythmic gene expression patterns as aging progresses. Collectively, our findings support that age-dependent rhythmic alteration of diurnal gene expression rhythms reprograms the timetable of daily gene expression, leading to the physiological changes required for plant senescence.